Sickle cell disease landscape and challenges in the EU: the ERN-EuroBloodNet perspective - Mañú Pereira, María del Mar; Colombatti, Raffaella; Alvarez, Federico; Bartolucci, Pablo; Bento, Celeste; Brunetta, Angelo Loris; Cela, Elena; Christou, Soteroula; Collado, Anna; de Montalembert, Mariane; Dedeken, Laurence; Fenaux, Pierre; et al. (The lancet. Haematology, 2023)
Sickle cell disease is a hereditary multiorgan disease that is considered rare in the EU. In 2017, the Rare Diseases Plan was implemented within the EU and 24 European Reference Networks (ERNs) were created, including the ERN on Rare Haematological Diseases (ERN-EuroBloodNet), dedicated to rare haematological diseases. This EU initiative has made it possible to accentuate existing collaborations and create new ones. The project also made it possible to list all the needs of people with rare haematological diseases not yet covered health-care providers in the EU to allow optimised care of individuals with rare pathologies, including sickle cell disease. This Viewpoint is the result of joint work within 12 EU member states (ie, Belgium, Cyprus, Denmark, France, Germany, Greece, Ireland, Italy, Portugal, Spain, Sweden, and The Netherlands), all members of the ERN-EuroBloodNet. We describe the role of the ERN-EuroBloodNet to improve the overall approach to and the management of individuals with sickle cell disease in the EU through specific on the pooling of expertise, knowledge, and best practices; the development of training and education programmes; the strategy for systematic gathering and standardisation of clinical data; and its reuse in clinical research. Epidemiology and research strategies from ongoing implementation of the Rare Anaemia Disorders European Epidemiological Platform is depicted.